2016
DOI: 10.1136/bmjopen-2015-010290
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene management among adolescent girls in India: a systematic review and meta-analysis

Abstract: Setting: India. Participants: Adolescent girls. Outcome measures: Information on menarche awareness, type of absorbent used, disposal, hygiene, restrictions and school absenteeism was extracted from eligible materials; a quality score was applied. Metaanalysis was used to estimate pooled prevalence (PP), and meta-regression to examine the effect of setting, region and time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
267
6
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(333 citation statements)
references
References 40 publications
(36 reference statements)
25
267
6
4
Order By: Relevance
“…9 When enquired about their opinion on menstruation, 60% urban and 40% tribal adolescent girls considered it to be a physiological, similar to a meta analysis on menstrual hygiene in India. 17 In a previous study, more girls became aware that menstruation is a normal process after they were imparted health education. 2 This observation highlights the importance of health education programmes in schools focussing mainly on menstrual hygiene and reproductive health among adolescent girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 When enquired about their opinion on menstruation, 60% urban and 40% tribal adolescent girls considered it to be a physiological, similar to a meta analysis on menstrual hygiene in India. 17 In a previous study, more girls became aware that menstruation is a normal process after they were imparted health education. 2 This observation highlights the importance of health education programmes in schools focussing mainly on menstrual hygiene and reproductive health among adolescent girls.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study and a meta analysis also revealed the same fact that sanitary pad use was more common in urban areas. 11,17 This may be due to the easy availability of menstrual hygiene products in urban settings and also the media which makes adolescent girls in urban areas more aware about these products. About 60% of total participants in this study opined that unnecessary restrictions should not be imposed during menstruation in contrast to a previous study where only 26% of girls had no restrictions imposed on them during periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt 21% of the total population comprises of adolescents [3]. Lack of adequate knowledge may lead to various genitourinary diseases among adolescent girls [4] Genitourinary tract infection is a bacterial infection that affects any part of the genital and urinary tract. occurs when too much bacteria especially those that inhabit the gastrointestinal tract and the skin enter the vagina through the anus and thrive inside the urinary system (kidney ,ureter, bladder and urethras) and consequently reproduce rapidly due to available nutrients [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Though available as one of the hygiene products in market since mid 20 th century, menstrual cup remained a stranger among women, often being neglected and rejected for the fear and unawareness of the method of usage [1]. The merits of these cups are many when compared to that of the conventional menstrual hygiene products, still it remains unexplored both in scientific research platform as well as in the layman knowledge ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%